A slow-cycling LGR5 tumour population mediates basal cell carcinoma relapse after therapy. (18th October 2018) - Sánchez-Danés, Adriana; Larsimont, Jean-Christophe; Liagre, Mélanie; Muñoz-Couselo, Eva; Lapouge, Gaëlle; Brisebarre, Audrey; Dubois, Christine; Suppa, Mariano; Sukumaran, Vijayakumar; del Marmol, Véronique; Tabernero, Josep; Blanpain, Cédric
Abstract Basal cell carcinoma (BCC) is the most frequent cancer in humans and results from constitutive activation of the Hedgehog pathway1 . Several Smoothened inhibitors are used to treat Hedgehog-mediated malignancies, including BCC and medulloblastoma2 . Vismodegib, a Smoothened inhibitor, leads to BCC shrinkage in the majority of patients with BCC3, but the mechanism by which it mediates BCC regression is unknown. Here we used two genetically engineered mouse models of BCC4 to investigate the mechanisms by which inhibition of Smoothened mediates tumour regression. We found that vismodegib mediates BCC regression by inhibiting a hair follicle-like fate and promoting the differentiation of tumour cells. However, a small population of tumour cells persists and is responsible for tumour relapse following treatment discontinuation, mimicking the situation found in humans5 . In both mouse and human BCC, this persisting, slow-cycling tumour population expresses LGR5 and is characterized by active Wnt signalling. CombiningLgr5 lineage ablation or inhibition of Wnt signalling with vismodegib treatment leads to eradication of BCC. Our results show that vismodegib induces tumour regression by promoting tumour differentiation, and demonstrates that the synergy between Wnt and Smoothened inhibitors is a clinically relevant strategy for overcoming tumour relapse in BCC. Treatment of basal cell carcinoma with Smoothened inhibitors leaves a small population of quiescent cells that can drive relapse but can be eliminated by additional treatment with a Wnt signalling inhibitor.